Modified method of DNA extraction from herbarium specimens (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The DNA isolation CTAB-method modified for seed plants herbarium material is proposed. Three modifications were tested on 29 samples from KW and KWU herbaria. Visual evaluation of optimal method is done for DNA containing pellet, PCR products (nuclear ITS and plastid rbcL gene sequence), amplicon sequencing with further comparing results obtained using those deposited in GenBank. The optimal variant of DNA extraction from herbarium material for different taxonomical groups of plants is proposed.
Keywords: herbarium specimens, DNA extraction, method modification.